Pengaruh Penggunaan Multimedia Interaktif dan Gaya Belajar Terhadap Hasil Belajar Bahasa Inggris - Suryanto Suryanto; Muhajir Muhajir; Kusmiyati Kusmiyati (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to analyze the effect of using interactive multimedia and learning styles on students' English learning outcomes. The research approach is a quantitative approach with a quasi-experimental research type. The subject of this research is class XI private high school in Driyorejo - Gresik sub-district in the odd semester of the 2019/2020 academic year. The sample was taken using purposive cluster sampling by considering the characteristics of the school and obtained two schools, namely SMA Raden Fatah as the control group and SMA AL-Furqon as the experimental group. The number of SMA Raden Fatah students is 36 students while SMA AL-Furqon is 39 students. In the learning process, the control group used powerpoint presentation media and the experimental group used flash-based interactive multimedia learning. The research data were collected through a learning style identification test and a student learning outcome test. Data were analyzed with the help of the SPSS 24 for windows program, with a two-way ANOVA test at a significance level of 0.05. The results of this study are that there is an effect of the use of interactive multimedia learning between groups of students with visual, auditory and kinesthetic learning styles together on students' English learning outcomes.